Pengaruh Kecerdasan Emosional dan Budaya Organisasi terhadap Kinerja Pegawai PT. Mitralab Buana dengan Motivasi sebagai Variabel Mediasi - Fauzan Hamdi Latif; Guswandi; Nino Nopriandi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2026)
This study aims to examine the effect of emotional intelligence and organizational culture on employee performance, both directly and indirectly through work motivation as a mediating variable at PT. Mitralab Buana. This study employs a quantitative method with a causal associative approach. Data were collected through questionnaires distributed to 49 respondents using a saturated sampling (census) technique. The data were analyzed using path analysis, including validity, reliability, classical assumption tests, and hypothesis testing. The results indicate that emotional intelligence and organizational culture have a positive and significant effect on employee performance. Emotional intelligence and organizational culture also have a positive and significant effect on work motivation. Furthermore, work motivation has a positive and significant effect on employee performance. However, work motivation is not able to mediate the relationship between emotional intelligence and organizational culture on employee performance at PT. Mitralab Buana